2000
DOI: 10.14411/fp.2000.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of condensed tannins from seven herbages on Trichostrongylus colubriformis larval migration in vitro

Abstract: Abstract. The effects of condensed tannins (CT) extracted from seven forages on the motility of the economically important nematode, Trichostrongylus colubriformis (Giles, 1892), were evaluated by using a larval migration inhibition (LMI) assay. The assay involved incubation of third stage (L3) exsheathed T. colubriformis larvae with CT extracted from Lotus pedunculatus, Lotus corniculatus, sulla (Hedysarum coronarium), sainfoin (Onobrychis viciifolia), Dorycnium rectum, Dorycnium pentaphyllum and dock (Rumex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 30 publications
10
67
0
10
Order By: Relevance
“…The objective was to avoid any bias in interpretation of results in relation to nutrition, since it has been repeatedly shown that any difference in host diets, and particularly in regard to protein components, might greatly influence the host response to nematode infections (Van Houtert and Sykes, 1996;Coop and Kyriazakis, 2001). In most studies on bioactive forages, it has been postulated that some plant secondary metabolites, and particularly condensed tannins, might present antiparasitic properties and this hypothesis has been substantiated by several in vivo (Athanasiadou et al, 2000a(Athanasiadou et al, ,b, 2001 or in vitro results (Molan et al, 2000a(Molan et al, , 2003a. On the other hand, it is important to note that during the week when hay was provided to goats, the consumption of sainfoin hay was significantly higher than for the rye grass one.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The objective was to avoid any bias in interpretation of results in relation to nutrition, since it has been repeatedly shown that any difference in host diets, and particularly in regard to protein components, might greatly influence the host response to nematode infections (Van Houtert and Sykes, 1996;Coop and Kyriazakis, 2001). In most studies on bioactive forages, it has been postulated that some plant secondary metabolites, and particularly condensed tannins, might present antiparasitic properties and this hypothesis has been substantiated by several in vivo (Athanasiadou et al, 2000a(Athanasiadou et al, ,b, 2001 or in vitro results (Molan et al, 2000a(Molan et al, , 2003a. On the other hand, it is important to note that during the week when hay was provided to goats, the consumption of sainfoin hay was significantly higher than for the rye grass one.…”
Section: Discussionmentioning
confidence: 95%
“…Several examples obtained from controlled indoor in vivo assays or from in vitro studies have been accumulated supporting the hypothesis for a role of plant secondary metabolites, and particularly condensed tannins, in these antiparasitic effects (Athanasiadou et al, 2003;Kahn and Diaz-Hernandez, 2000;Molan et al, 2000aMolan et al, ,b, 2003a. In sheep, several studies have shown that the consumption of some bioactive, legume forages like sulla (Hedysarium coronarium), maku (Lotus pedunculatus) or birdsfoot trefoil (Lotus corniculatus) were associated with some positive effects on the host resilience and/or host resistance to parasite infection (Niezen et al, 1995(Niezen et al, , 1998aMarley et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The total effect was observed for all concentrations on the level of 22-87% and for a concentration of 1000 µg/mL, ranging from 27% to 63%. We can compare the result with the LMI test performed with seven plant extracts against the larvae of T. colubriformis, where at the same concentration (1000 µg/mL), the range was from 37% to 63% (Molan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…At the rumen level, the optimal concentration of CTs to reduce proteolysis in vitro has been set at about 400 mg CTs per ml and above (Aerts et al, 1999). The same concentration reduced the growth of several bacterial strains from the rumen (Molan et al, 2000).…”
Section: Figurementioning
confidence: 95%